2013
DOI: 10.1021/la4008729
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Structure of a DOPA-Inspired Adhesive Polymer Studied by Sum Frequency Generation Vibrational Spectroscopy

Abstract: Marine mussels deposit adhesive proteins containing 3,4-dihydroxyphenylalanine (DOPA) to attach themselves to different surfaces. Isolating such proteins from biological sources for adhesion purposes tends to be challenging. Recently, a simplified synthetic adhesive polymer, poly[(3,4-dihydroxystyrene)-co-styrene] (PDHSS), was developed to mimic DOPA-containing proteins. The pendant catechol group in this polymer provides cross-linking and adhesion much like mussel proteins do. In this work, sum frequency gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
51
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 61 publications
0
51
0
Order By: Relevance
“…polyolefin, polystyrene (PS)) ( Fig. 2f) [68,69]. However, although a possible deposition process was proposed [70], the mechanism remains elusive for some hydrophobic substrates with low surface energy, such as polytetrafluoroethylene (PTFE) and PP, which may be rationalized by hydrophobic interactions [65].…”
Section: Structures and Adhesion Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…polyolefin, polystyrene (PS)) ( Fig. 2f) [68,69]. However, although a possible deposition process was proposed [70], the mechanism remains elusive for some hydrophobic substrates with low surface energy, such as polytetrafluoroethylene (PTFE) and PP, which may be rationalized by hydrophobic interactions [65].…”
Section: Structures and Adhesion Mechanismsmentioning
confidence: 99%
“…12f-h). The adhesion strength between skin layer and support layer was surp;risingly strong due to the π-π interaction [68] and the dense composite membrane exhibited excellent stability and desirable durability for prevaporative desulfurization process. The fractional free volume, an important factor for separation performance, could be adjusted by changing the dopamine concentration.…”
Section: Skin Layermentioning
confidence: 99%
“…However, it is difficult to synthesize bioadhesives that can be applied in aqueous environments that are resistant to water and wave impacts; this is due to the existence of a weak boundary layer of water at the interfaces between the adherend and substrates or to the swelling of the adhesive by water absorption [6]. Marine mussels (mytilus edulis), such as the blue mussel, attach to a variety of surfaces in aqueous environments through the use of a natural adhesive that is incredibly strong and can form durable bonds to glass, plastic, wood, concrete, and Teflon [1,[7][8][9]]. Marine mussels withstand high-energy wave impacts in rocky seashore habitats by fastening tightly to surfaces with tough and self-healing proteinaceous fibers, called byssal threads, composed of 25-30 different types of underwater mussel adhesive proteins (UMAPs) [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of MFP-inspired adhesives have been investigated on pristine surfaces in solution (18)(19)(20)(21)(22); however, under more realistic conditions, surfaces targeted for adhesion are rarely free from contaminants and are fouled with organic films that impede robust adhesion. Yu et al (17) demonstrated that certain MFPs promote strong adhesion to hydrophobic self-assembled monolayers (SAMs), presumably through direct interactions with the surface, while exhibiting weak adhesion to hydrophilic SAMs.…”
mentioning
confidence: 99%